2019
DOI: 10.1002/cssc.201901519
|View full text |Cite
|
Sign up to set email alerts
|

High Capacitive Energy Storage of Nest‐Like Porous Graphene Microspheres Electrode with High Mass Loading

Abstract: Nest‐like porous graphene microspheres (NPGMs) are grown by using a chemical vapor deposition (CVD) method in a fluidized bed reactor from methane and basic magnesium carbonate microspheres (synthesized by a stirring‐induced crystallization approach) as carbon source and template, respectively. The CVD‐derived NPGMs have a few‐layer structure and high electrical conductivity, as well as a three‐dimensional individual macroarchitecture accompanied with well‐developed pore channels and great structural integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Data on the gravimetric specific capacitance of some electrode materials in different mass-loadings reported in the literature , are collected and listed in Table S1, and corresponding relations between the specific capacitance and the mass-loading are also shown in Figure . Obviously, it is shown that (1) the specific capacitance decreases with increasing the mass-loadings, while the decreasing degree in the low mass-loading range is much larger than in the high mass-loading range; (2) the change tendency is seemingly uncorrelated to the storage energy mechanisms of the materials together with electrolytes, but for some PC materials the mass-loading effect is more prominent; and (3) measured values of the specific capacitance depend on the current density and scan rate especially at high mass-loadings.…”
Section: Practice Guidelines For the Mass-balancingmentioning
confidence: 99%
“…Data on the gravimetric specific capacitance of some electrode materials in different mass-loadings reported in the literature , are collected and listed in Table S1, and corresponding relations between the specific capacitance and the mass-loading are also shown in Figure . Obviously, it is shown that (1) the specific capacitance decreases with increasing the mass-loadings, while the decreasing degree in the low mass-loading range is much larger than in the high mass-loading range; (2) the change tendency is seemingly uncorrelated to the storage energy mechanisms of the materials together with electrolytes, but for some PC materials the mass-loading effect is more prominent; and (3) measured values of the specific capacitance depend on the current density and scan rate especially at high mass-loadings.…”
Section: Practice Guidelines For the Mass-balancingmentioning
confidence: 99%
“…Besides, this structure also allows disordered ions to travel through it efficiently under highloading conditions. 20 Fu et al prepared pore-rich and superwetted N/O/B triple-doped 2D carbon nanosheets using waste sweet potato leaves and boric acid (B 1 -SC), and the material exhibited a good specific capacitance of 296 F g −1 at 0.5 A g −1 in SCs. 21 Even with the addition of heteroatoms and a 2D, ultra-thin, and super-hydrophilic porous structure, the device is still prone to material stacking and collapses during operation, leaving poor electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…The open 3D porous structure provides not only high SSA and abundance of quadratic active sites but also a big ion electrode/electrolyte contact interface and low impedance, which can significantly increase energy density. Besides, this structure also allows disordered ions to travel through it efficiently under high-loading conditions . Fu et al prepared pore-rich and super-wetted N/O/B triple-doped 2D carbon nanosheets using waste sweet potato leaves and boric acid (B 1 -SC), and the material exhibited a good specific capacitance of 296 F g –1 at 0.5 A g –1 in SCs .…”
Section: Introductionmentioning
confidence: 99%